The reduction of human development gap in origin and new regency in Eastern Indonesia - Jihad Lukis Panjawa; Bhimo Rizky Samudro (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Inequality still becomes popular issue in the establishment of developing countries. Aside from the income inequality, the human development inequality is considered as an interesting topic for further study, in terms of resuming the solution. The purpose of this study is considered as specific in identifying the human development gap between origin and new regencies in Eastern Indonesia as well as the determinant. This study uses a positivist perspective with a deductive approach. Secondary data with cross-section types used in this study covers regencies and cities in Eastern Indonesia. This study uses the econometrics methodology using regression analysis with a dummy variable. The results showed there were differences in human development index between origin and new regencies in Eastern Indonesia. The human development index in the new regency is lower than in the origin regency. The results support the Myrdal’s Theory, which explains the gap in human development disparities among regions due to the significant backwash effects. Fiscal decentralization has a role in reducing the gap in human development in origin and new regencies, yet insignificant for the economic growth. Poverty lowers the impact on increasing human development in the origin regencies but does not occur in the new regencies.JEL Classification  H30; I32; O15